PENCOCOKAN KATA SECARA ACAK DENGAN METODE ALGORITMA GENETIKA MENGGUNAKAN PROGRAM PASCAL - Mulia Afriani Kartika (Jurnal Matematika UNAND, 2013)
The Genetic Algorithm was introduced independently for the rst time byHolland and De Jong in 1975. This algorithm is the stochastic optimization techniquesbased on the principle from evolution theory. Since then, numerous applications of ge-netic algorithm have been developed in many areas, such as scheduling and sequencing,reliability design, road network, and many others. This paper is addressed to discusssome steps performed in genetic algorithm processes. We also give an example of thealgorithm in word matching randomly using Pascal programming, which specically de-veloped for academic purposes. Some factors that inuence the accuracy of the resultingword matching at random is also explained in detail by running Pascal program repeat-edly.